Putative Serine Protease Effectors of Clavibacter michiganensis Induce a Hypersensitive Response in the Apoplast of Nicotiana Species - You Lu; Noriyuki Hatsugai; Fumiaki Katagiri; Carol A. Ishimaru; Jane Glazebrook (Molecular Plant-Microbe Interactions, 2015)
Clavibacter michiganensis subspp. michiganensis and sepedonicus cause diseases on solanaceous crops. The genomes of both subspecies encode members of the pat-1 family of putative serine proteases known to function in virulence on host plants and induction of hypersensitive responses (HR) on nonhosts. One gene of this family in C. michiganensis subsp. sepedonicus, chp-7, is required for triggering HR in Nicotiana tabacum. Here, further investigation revealed that mutation of the putative catalytic serine residue at position 232 to threonine abolished the HR induction activity of Chp-7, suggesting that enzymatic activity is required. Purified Chp-7 triggered an HR in N. tabacum leaves in the absence of the pathogen, indicating Chp-7 itself is the HR elicitor from C. michiganensis subsp. sepedonicus. Ectopic expression of chp-7 constructs in N. tabacum leaves revealed that Chp-7 targeted to the apoplast triggered an HR while cytoplasmic Chp-7 did not, indicating that Chp-7 induces the HR in the apoplast of N. tabacum leaves. Chp-7 also induced HR in N. sylvestris, a progenitor of N. tabacum, but not in other Nicotiana species tested. ChpG, a related protein from C. michiganensis subsp. michiganensis, also triggered HR in N. tabacum and N. sylvestris. Unlike Chp-7, ChpG triggered HR in N. clevelandii and N. glutinosa.